2017
DOI: 10.1158/0008-5472.can-16-2913
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Autocrine CCL5–CCR5 Axis Reprograms Immunosuppressive Myeloid Cells and Reinvigorates Antitumor Immunity

Abstract: The tumor-promoting potential of CCL5 has been proposed but remains poorly understood. We demonstrate here that an autocrine CCL5-CCR5 axis is a major regulator of immunosuppressive myeloid cells (IMC) of both monocytic and granulocytic lineages. The absence of the autocrine CCL5 abrogated the generation of granulocytic myeloid-derived suppressor cells and tumor-associated macrophages. In parallel, enhanced maturation of intratumoral neutrophils and macrophages occurred in spite of tumor-derived CCL5. The refr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 49 publications
2
101
2
Order By: Relevance
“…Of note, immunosuppressive G‐MDSC accumulation into tumor sites can also rely on host‐derived factors. Ban et al., for example, showed that the altered neutrophil maturation and G‐MDSC accumulation in the primary tumors of 4T1 and PyMT murine breast tumors are controlled by myeloid CCR5 and an autocrine CCR5‐CCL5 axis, but not by tumor‐derived CCL5. In the absence of host CCL5, neutrophils similar to N1 TANs are recruited into tumors .…”
Section: Neutrophil Subsets In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, immunosuppressive G‐MDSC accumulation into tumor sites can also rely on host‐derived factors. Ban et al., for example, showed that the altered neutrophil maturation and G‐MDSC accumulation in the primary tumors of 4T1 and PyMT murine breast tumors are controlled by myeloid CCR5 and an autocrine CCR5‐CCL5 axis, but not by tumor‐derived CCL5. In the absence of host CCL5, neutrophils similar to N1 TANs are recruited into tumors .…”
Section: Neutrophil Subsets In Cancermentioning
confidence: 99%
“…Ban et al., for example, showed that the altered neutrophil maturation and G‐MDSC accumulation in the primary tumors of 4T1 and PyMT murine breast tumors are controlled by myeloid CCR5 and an autocrine CCR5‐CCL5 axis, but not by tumor‐derived CCL5. In the absence of host CCL5, neutrophils similar to N1 TANs are recruited into tumors . Taken together, these studies show that functional plasticity exists among neutrophils along their course of maturation during tumorigenesis and tumor progression.…”
Section: Neutrophil Subsets In Cancermentioning
confidence: 99%
“…Additional cancer neutrophil makers are gaining attention in their ability to distinguish maturation state (c‐kit or CD117, CXCR2, CD101, CCR5), or oxidative and inflammatory activity (lectin‐type oxidized LDL receptor 1 (LOX‐1), CXCR4, CD177) (Fig. ) …”
Section: Markers For Neutrophil Subsets In Cancermentioning
confidence: 99%
“…The tumor phenotype likely regulates the type of neutrophil brought within the tumor microenvironment . Cancer cells and cancer‐supporting fibroblasts can secrete mediators such as IL‐8 and CXCL1/2/5 that recruit mature CXCR2 + neutrophils; c‐kit‐ligand (SCF) that recruits immature c‐kit + neutrophils; or CCL5 that recruits immature CCR5 hi neutrophils . Tumors also release granulopoiesis‐inducing factors such as G‐CSF, SCF, GM‐CSF that support neutrophil production and survival (Fig.…”
Section: Recruitment Of Neutrophils To the Tumor Microenvironmentmentioning
confidence: 99%
“…[1621] The released therapeutics can affect not only cancer cells but also immune cells, consequently modifying the tumor microenvironment. [22] Nanotechnology-based cancer vaccines promote rapid expansion of tumor-specific T cells, and various forms of nanoparticles (NPs) have been utilized in the generation of therapeutic T cells for adoptive T cell therapies. Furthermore, multiple laboratories have applied nanotechnology-based approaches to unleash the activities of TILs by suppressing the activities of immune checkpoint inhibitor proteins, regulatory T (Treg) cells, and immunosuppressive myeloid cells (IMCs), by mimicking tumor-associated leukocytes, and by altering the tumor extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%